Phonon modes and local polar distortions in nanoclusters of Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 crystals probed by terahertz reflectance spectra and Raman scattering. (20th April 2015) - Zhu, J J; Zhang, J Z; Xu, G S; Zhang, X L; Hu, Z G; Chu, J H
Abstract: Optic phonons and lattice vibrations of Pb(In1/2 Nb1/2 )O3 -Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 single crystals near the morphotropic phase boundary (MPB) are determined by terahertz (THz) reflectance spectra in a temperature range of 5.5–300 K. Raman scattering is measured with a He–Ne laser with a wavelength of 632.8 nm as the exciting source. On cooling from 300 K, the A 1 component of the splitting TO1 mode hardens, which follows the Cochran law with a critical softening temperature of 761–861 K. Moreover, the E component of the soft mode is heavily damped around 0.81 THz (27 cm − 1 ). Additional polar phonon modes, which are forbidden in the cubic structure, are activated due to the broken cubic symmetry in polar clusters.